ELAVL1 Modulates Transcriptome-wide miRNA Binding in Murine Macrophages - Yi-Chien Lu; Sung-Hee Chang; Markus Hafner; Xi Li; Thomas Tuschl; Olivier Elemento; Timothy Hla (Cell Reports, 2014)
Posttranscriptional gene regulation by miRNAs and RNA binding proteins (RBP) is important in development, physiology, and disease. To examine the interplay between miRNAs and the RBP ELAVL1 (HuR), we mapped miRNA binding sites at the transcriptome-wide scale in wild-type and Elavl1 knockout murine bone-marrow-derived macrophages. Proximity of ELAVL1 binding sites attenuated miRNA binding to transcripts and promoted gene expression. Transcripts that regulate angiogenesis and macrophage/endothelial crosstalk were preferentially targeted by miRNAs, suggesting that ELAVL1 promotes angiogenesis, at least in part by antagonism of miRNA function. We found that ELAVL1 antagonized binding of miR-27 to the 3′ UTR of Zfp36 mRNA and alleviated miR-27-mediated suppression of the RBP ZFP36 (Tristetraprolin). Thus, the miR-27-regulated mechanism synchronizes the expression of ELAVL1 and ZFP36. This study provides a resource for systems-level interrogation of posttranscriptional gene regulation in macrophages, a key cell type in inflammation, angiogenesis, and tissue homeostasis.